Analysis of Types of Technology Use as a Supporting Tool for Sociology Learning by High School Students - Fathan Syuhada Kurniawan; Sariyatun; Herry Widyastono (Journal of Education Technology, 2022)
Today's findings must refer to the four attributes of 21st-century learning: specific reasoning and critical thinking, imagination, progress, joint effort, and correspondence. 21st-century learning requires discoveries that are open and versatile to today's changing mechanical events. Therefore, this research aims to analyze the types of technology used by teachers to support the sociology learning process. In this study, the method used is the descriptive qualitative method. Data collection techniques used were surveys and interviews referring to questionnaires and interview guidelines as research instruments. The research subjects consisted of 145 high school students. The data obtained will then be analyzed interactively with 4 stages. The research results show that 95% of students are identified as having a smartphone. It is also supported by regulations at school that allow the use of smartphones for learning activities. It is just that this opportunity has challenges where students still tend to use smartphones to play games (48% of student respond). Seeing these opportunities and challenges, smartphones are a type of technology that can be optimized for sociology learning activities independently and in groups. Thus students can divert the use of smartphones as a means of playing, becoming a tool to support learning facilitated by the teacher.